2022
DOI: 10.1038/s41467-022-28427-0
|View full text |Cite
|
Sign up to set email alerts
|

Tousled-like kinase 2 targets ASF1 histone chaperones through client mimicry

Abstract: Tousled-like kinases (TLKs) are nuclear serine-threonine kinases essential for genome maintenance and proper cell division in animals and plants. A major function of TLKs is to phosphorylate the histone chaperone proteins ASF1a and ASF1b to facilitate DNA replication-coupled nucleosome assembly, but how TLKs selectively target these critical substrates is unknown. Here, we show that TLK2 selectivity towards ASF1 substrates is achieved in two ways. First, the TLK2 catalytic domain recognizes consensus phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…In order to validate the analysis results of differentially expressed genes, the expression levels of three differentially expressed genes in sperm samples of the experimental group and control group related to sperm DNA damage and repair, including PMS1, TP53BP1 and TLK2, were detected by RT-qPCR. Tousled-like kinases (TLKs) are nuclear serine-threonine kinases essential for genome stability, proper cell division and normal development in numerous organisms (Simon et al, 2022), whose activity has been linked to DNA replication, DNA repair, chromatin structure and etc. (Segura-Bayona et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In order to validate the analysis results of differentially expressed genes, the expression levels of three differentially expressed genes in sperm samples of the experimental group and control group related to sperm DNA damage and repair, including PMS1, TP53BP1 and TLK2, were detected by RT-qPCR. Tousled-like kinases (TLKs) are nuclear serine-threonine kinases essential for genome stability, proper cell division and normal development in numerous organisms (Simon et al, 2022), whose activity has been linked to DNA replication, DNA repair, chromatin structure and etc. (Segura-Bayona et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2a, b ). Apart from the kinase activity, Tousled-Like kinase 2 also acts as an ASF1 regulator by mimicking H3 and recognizing ASF1’s H3-H4 binding pocket 43 . Although the two ASF1 proteins shared most of the interacting partners, we did not observe physical interaction between them, suggesting that in Arabidopsis, two mutually exclusive HIRA complexes may exist depending on whether they include ASF1A or ASF1B.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that FAM20C might be a biomarker for diverse cancers, including triple-negative breast cancer ( Tagliabracci et al, 2015 ), lung adenocarcinoma ( Li H. et al, 2020 ), and stomach adenocarcinoma ( Liu et al, 2021 ). TLK2 , a nuclear serine-threonine kinase, binds at the H3 binding site to promote ASF1 (histone chaperone protein anti-silencing factor 1) phosphorylation and cell growth ( Simon et al, 2022 ). TLK2 amplifies and serves as an oncogene in multiple diseases ( Kim et al, 2016 ; Lelieveld et al, 2016 ; Kuczler et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%